2018
DOI: 10.1155/2018/5025143
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Depression among Orphan Adolescents in Addis Ababa, Ethiopia

Abstract: Background Orphan adolescents are a special group of people who are generally deprived and prone to develop psychiatric disorder even if reared in a well-run institution. Objective To assess the prevalence and associated factors of depression among orphan adolescents living in Addis Ababa orphan centers, Addis Ababa, Ethiopia. Method A cross-sectional study was conducted in 2016 among 453 orphan adolescents in Ethiopia. All orphan adolescents who were living in the selected orphan centers were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 24 publications
4
15
1
2
Order By: Relevance
“…Being female, drinking alcohol, presence of congenital diseases, low social support, and getting bullied were found to be factors significantly associated with depressive symptoms among this population. The presence rate of depressive symptoms found in the current study was lower compared with the presences reported by studies among adolescents in Ethiopia (36.4%) [29], India (46.0-53.0%) [30], and the Gaza Strip 67.9% [12], which are also developing countries. In the developed country of Japan, 43.3% [31] of children in residential foster care were found to have depressive symptoms; however, a systematic review reported that the prevalence of the depressive disorder in children in the Japanese child welfare system was 11.0% [32].…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Being female, drinking alcohol, presence of congenital diseases, low social support, and getting bullied were found to be factors significantly associated with depressive symptoms among this population. The presence rate of depressive symptoms found in the current study was lower compared with the presences reported by studies among adolescents in Ethiopia (36.4%) [29], India (46.0-53.0%) [30], and the Gaza Strip 67.9% [12], which are also developing countries. In the developed country of Japan, 43.3% [31] of children in residential foster care were found to have depressive symptoms; however, a systematic review reported that the prevalence of the depressive disorder in children in the Japanese child welfare system was 11.0% [32].…”
Section: Discussioncontrasting
confidence: 89%
“…The variations in the presences of depressive symptoms found in these studies can partly be explained by differences in sample size, study population, and different methods of assessment. Most of the studies [29,30] considered only the orphan population, whereas the current study included all children or adolescents living in CCHs, which more accurately reflects the true situation in a Nepalese context. Moreover, there were variations in the criteria used to categorize depression and in the depression measurement tools.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, orphan children as compared to nonorphans are more vulnerable to severe depression and are at risk of what appears to be clinical depression. 9,40 These findings are corroborated in existing literature in which orphaned children living in the Gaza strip had considerable posttraumatic stress disorder, anxiety, and depression. 31 Likewise, another study confirmed high prevalence of depression among orphans and identified low level of social support, higher length of stay, community discrimination, the presence of visitors, and younger age of entrance were statistically significant variables to develop depression.…”
Section: Discussionsupporting
confidence: 79%
“…and non-orphans decision-making skills are hindered by feelings of anxiety, depression, and low self-esteem while interacting with others in social settings. 18,[37][38][39] In the present study, there is significant correlation of stress and depression with decision-making. Similarly, orphan children as compared to nonorphans are more vulnerable to severe depression and are at risk of what appears to be clinical depression.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation